2016
DOI: 10.1080/14397595.2016.1179860
|View full text |Cite
|
Sign up to set email alerts
|

The growth factor midkine may play a pathophysiological role in rheumatoid arthritis

Abstract: The serum MK level could be a marker of disease activity in RA and an indicator of a poor prognosis. MK may have a role in the pathogenesis of RA via induction of inflammatory mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 33 publications
5
38
1
Order By: Relevance
“…Therefore, these findings suggest that serum Midkine level could be a useful marker for RA disease activity. However, contradictory to our results, the RF high titer was found to be correlated with the serum Midkine in several studies that suggest its relation with the poor prognosis of RA 18 21 26…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Therefore, these findings suggest that serum Midkine level could be a useful marker for RA disease activity. However, contradictory to our results, the RF high titer was found to be correlated with the serum Midkine in several studies that suggest its relation with the poor prognosis of RA 18 21 26…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, we suggest that serum Midkine may be useful in the diagnosis of RA and to detect the disease activity. In agreement with our results, a study conducted by Shindo et al ,21 detected a high level of serum Midkine in patients with RA and the overexpression of Midkine protein and mRNA in RA synovial tissues as well as the cultured rheumatoid synovial fibroblasts (RSFs). Previous functional studies detected that Midkine is significantly upregulated in inflamed synovial tissue during an active RA flare in contrast to synovial tissue of healthy patients 16.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Plasma MK was elevated in patients with systemic lupus erythematosus which was correlated with IL-17 (11). In rheumatoid arthritis (RA) patients, high MK levels were found to implicated in the pathogenesis of RA and was associated with IL-6 and IL-8 (12,13). In acute and chronic kidney injuries like ischemia/reperfusion injury and diabetic nephropathy, the expression of MK was upregulated and promotes migration of neutrophils and macrophages, hence MK deficiency may show less renal damage (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Midkine has been proved to be elevated both in plasma and tissues during sepsis [11,12], however, its effects on the organ function was under debate, midkine seemed to have an organ-dependent effect, which showed a protective effect in acute cardiac infarction [28], with angiogenesis promotion [29] and vascular endothelial repairment [30], but a deleterious effect in kidney [31], lung injury [32,33] and autoimmune diseases [34]. In the present study, we found high circulating midkine was correlated to the severity lung injury induced by sepsis.…”
Section: Discussionmentioning
confidence: 99%